Anaerosphaera massiliensis sp. nov., a new bacterium isolated from the stool of a 39-year-old Pygmy. (January 2020) - Takakura, T.; Francis, R.; Anani, H.; Bilen, M.; Raoult, D.; Bou Khalil, J.Y.
Abstract: Anaerosphaera massiliensis strain Marseille-P4592 T (= CSURP4592 T ; = CCUG72452 T ) is a new species isolated from the stool of a 39-year-old male Pygmy from the Democratic Republic of Congo.